The Role of Virtual Reality in Enhancing Skill-Based Training Programs - Mehta, Amitabh Rohan; Verma, Sanjana Devi; Yadav, Arjun Pratap (Etunas Sukses Sistem, 2022)
Virtual Reality (VR) has emerged as a transformative technology in skill-based training programs, offering immersive and interactive learning environments that enhance practical competencies across various industries. This paper explores the role of VR in improving training effectiveness, engagement, and knowledge retention. By simulating real-world scenarios, VR enables learners to practice tasks in a safe and controlled setting, reducing the risks and costs associated with traditional hands-on training. The study examines key benefits, such as enhanced experiential learning, personalized feedback, and scalability, while also addressing challenges like hardware limitations, development costs, and user adaptability. Through a review of existing research and case studies, this article highlights the growing adoption of VR in fields such as healthcare, manufacturing, and aviation, demonstrating its potential to revolutionize modern training methodologies. The findings suggest that integrating VR into skill-based training programs can significantly improve learning outcomes, making it a valuable tool for workforce development in the digital age.